2007
DOI: 10.1016/j.jconrel.2007.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Particle shape: A new design parameter for micro- and nanoscale drug delivery carriers

Abstract: Encapsulation of therapeutic agents in polymer particles has been successfully used in the development of new drug carriers. A number of design parameters that govern the functional behavior of carriers, including the choice of polymer, particle size and surface chemistry, have been tuned to optimize their performance in vivo. However, particle shape, which may also have a strong impact on carrier performance, has not been thoroughly investigated. This is perhaps due to the limited availability of techniques t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
834
1
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 1,106 publications
(851 citation statements)
references
References 39 publications
4
834
1
12
Order By: Relevance
“…Recreation of the complex morphology of RBCs in a synthetic system has proved challenging using currently established techniques (20). We adopted a biomimetic strategy to prepare RBC-shaped particles.…”
Section: Resultsmentioning
confidence: 99%
“…Recreation of the complex morphology of RBCs in a synthetic system has proved challenging using currently established techniques (20). We adopted a biomimetic strategy to prepare RBC-shaped particles.…”
Section: Resultsmentioning
confidence: 99%
“…The motivation to develop particles with switchable shapes comes from the fact that shape has recently emerged as a crucial design parameter of micro-and nanoparticles (3,4,33,38,39). Studies have demonstrated that departure from the conventional spherical shape of particles brings unique and improved functionalities to the particulate systems, resulting in improved biological responses.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of these interactions relies on optimal selection of key particle properties including surface chemistry, size, and shape (3,4). Accordingly, numerous studies have reported on methods to synthesize materials with precisely engineered functional attributes such as size, surface chemistry, mechanical properties, and shape to facilitate or mitigate interactions with various cell types (3)(4)(5).…”
mentioning
confidence: 99%
“…However, the movements of non-spherical (anisotropic) particles are much more complex because such particles may align or tumble inside a fl uidic stream. [ 88 ] For example, fi lamentous fl exible micelles (fi lomicelles from di-block copolymers such as poly(ethylene glycol)-poly(caprolactone) (PEG-PCL) and poly(ethylene glycol)-poly(ethyl ethylene) (PEG-PEE)) remain in the blood circulation for more time than spherical and shorter fi lomicelles due to their alignment with the blood fl ow. [ 95 ] Diskshaped liposomes also demonstrated higher circulation time when compared with spherical counterparts.…”
Section: Effect On Circulation and Biodistributionmentioning
confidence: 99%